2011
DOI: 10.1007/s12033-011-9489-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analysis of Two Osmotin (PR5) Isoforms with Differential Antifungal Activity from Piper colubrinum: Prediction of Structure–Function Relationship by Bioinformatics Approach

Abstract: Osmotin, a pathogenesis-related antifungal protein, is relevant in induced plant immunity and belongs to the thaumatin-like group of proteins (TLPs). This article describes comparative structural and functional analysis of the two osmotin isoforms cloned from Phytophthora-resistant wild Piper colubrinum. The two isoforms differ mainly by an internal deletion of 50 amino acid residues which separates them into two size categories (16.4 kDa-PcOSM1 and 21.5 kDa-PcOSM2) with pI values 5.6 and 8.3, respectively. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Osmotin and its various isoforms have been cloned from many plants (Capelli et al 1997, Pla et al 1998, Jami et al 2007, Singh et al 2017, Mani et al 2012, Li et al 2015. The presence of osmotin isoforms in same plant have been previously reported in Piper colubrinum (Mani et al 2012). The two isoforms were reportedly distinct from each other in terms of size, pI value and molecular structure.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Osmotin and its various isoforms have been cloned from many plants (Capelli et al 1997, Pla et al 1998, Jami et al 2007, Singh et al 2017, Mani et al 2012, Li et al 2015. The presence of osmotin isoforms in same plant have been previously reported in Piper colubrinum (Mani et al 2012). The two isoforms were reportedly distinct from each other in terms of size, pI value and molecular structure.…”
Section: Resultsmentioning
confidence: 92%
“…Generally, the presence of 16 cysteine residues have been reported in osmotin (Kumar et al 2015), but in the present study, only 15 cysteine residues were present which lead to formation of 7 disulphide bridge only (Figure 3). The presence of disulphide bridges is known to provide high stability to the protein (Mani et al 2012). The instability index (II) calculated for OsmSt1 and OsmSt2 using ProtPram tool of Expasy server were found to be about 38.90 which indicates that the proteins are highly stable (https://web.expasy.org/protparam/).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, it was showed that abscisic acid (ABA), low temperature and NaCl can induce the accumulation of three StOSM mRNAs (pA13, pA35, and pA81) in S. commersonii grown in vitro (Zhu et al 1995). Later on StOSM was shown to exhibit antifungal activity against a range of fungal pathogens (Rivero et al 2012, Mani et al 2012and Patade et al 2013. Recently, StOSM overexpression in transgenic Arabidopsis and pepper results in H 2 O 2 accumulation and the response of hypersensitive cell death in the leaf and reduces susceptibility to pathogen infection (Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%